Literature Review of Pandemic covid 19 Effects on Employee Compensation - Safuan Safuan; Tedi Kurnia (Profesional Muda Cendekia Publishing, 2021)
This article aims to determine the development of research on compensation during the Covid 19 pandemic in Indonesia. The method used is a qualitative method by conducting a literature study or literature review. The application used for the literature study is google scholar with the keyword